Occurrence of the leaf-cutters ants in the high-altitude grasslands in the south Brazil - Giesel, Alexandre (2020)
Remnants of the Campos Altitude ecosystem are found in the "Campos de Lages" micro-region, SC, southern Brazil. The objective of this work was to evaluate and identify species of leaf-cutter ants that occur in Campos de Altitude. The study was conducted between the months of August 2012 and December 2013, in 18 municipalities of the micro-region of "Campos de Lages", Santa Catarina, southern Brazil. In total, 75 cutter anthills were located, measured and georeferenced, which presented 16 anthills belonging to the genus Atta and 59 to the genus Acromyrmex. Samples of ants from different castes were collected from each anthill for proper identification. One species has been identified in the genus Atta, A. sexdens piriventris and eight in the genus Acromyrmex, Ac. laticeps, Ac. heyeri, Ac. Iundii, Ac. crassispinus, Ac. ambiguus, Ac. aspersus, Ac. coronatus. The species Atta sexdens piriventris, Ac. laticeps and Ac. heyeri, were the most frequent. Species belonging to the genus Acromyrmex were located at altitudes above 1000 meters, and average anthills size of 1.04 ± 0.93 m2. Atta anthills were located at altitudes of up to 850 meters, and had an average size of 132.75 ± 12.96 m2 of total surface area, considering the area of entrance roles.